Model of Reducing Job Burnout in Human Resources in State Organizations Using a Meta-Synthesis Approach - Mohammad javad Vahedasrami; Mojtaba Tabari; Asadollah Mehrara (پژوهش‌های مدیریت عمومی, 2022)
Abstract One of the most basic needs of employees in any organization is to ensure their physical and mental health in the workplace; in such a way that severe physical and psychological stress due to the nature, type or inappropriate state of work can lead to a condition in employees that is known as job burnout. The occurrence of this phenomenon can have negative consequences for individuals and even organizations; therefore, the present study was conducted with the aim of presenting a model of reducing job burnout in human resources in state organizations using a meta-synthesis approach. For this purpose, after searching in databases in the period of 2000 to 2020 and 1380 to 1400, finally 38 studies that were closely related to the subject under study were selected and by analyzing their content, the relevant dimensions and codes were extracted and the importance and priority of each it was determined using Shannon entropy method. Based on the research findings, the factors affecting the reducing job burnout in human resources in state organizations of the country were placed in three categories: "organizational factors", "occupational factors" and "individual factors". Also, among the identified codes, existence of field of education and continuous opportunities in the organization, existence of sincere atmosphere in the organization, independence and freedom of action in the job, existence of opportunities for promotion and career advancement at work, having a sense of effectiveness at work, satisfaction with pay, having emotional stability in different situations and managing yourself in the face of emotional reactions, gained the highest coefficient of importance.